International legal research - Williams, John; International Law Students Association; American Society of International Law1 Hodge, Denise M.1 Green, Jonathan Clark (Washington, D.C. : International Law Students Association, 1989)
The program is about how to carry legal research on international law
Executive producers, Denise M. Hodge, Jonathan Clark Green
Keywords: International law -- Legal research